Adenocarcinoma of the esophagogastric junction and its background mucosal pathology: A comparative analysis according to Siewert classification in a Japanese cohort. (21st September 2018) - Urabe, Masayuki; Ushiku, Tetsuo; Shinozaki‐Ushiku, Aya; Iwasaki, Akiko; Yamazawa, Sho; Yamashita, Hiroharu; Seto, Yasuyuki; Fukayama, Masashi
Abstract: Adenocarcinoma of the esophagogastric junction (AEG) has heterogeneous carcinogenic process due to its location straddling the esophagogastric junction. We assessed background mucosal pathology and its correlation with clinicopathological features of each Siewert type of AEG. Clinicopathological and immunohistochemical analyses of 103 AEGs and 58 gastric cancers (GCs) were conducted. Background mucosal features were evaluated according to the updated Sydney System. Siewert classification divided 103 AEGs into three type I, 75 type II, and 25 type III tumors, respectively. Two type I, 9 type II AEGs, and none of type III AEGs were Barrett‐related and were excluded from further analysis. Background mucosa of type III AEGs more frequently showed moderate to marked degree of atrophy and intestinal metaplasia than those of type II AEGs and was very similar to those of GCs. Among type II AEGs, tumors with atrophic background were significantly associated with higher patient age and intestinal‐type histology. Type II AEGs with nonatrophic background, but not those with atrophic background, showed more frequent mismatch repair deficiency, TP53 overexpression, and less frequent intestinal phenotypic markers expression than type III AEG or GC. Type II AEGs with atrophic background involved suprapancreatic nodes more frequently than those without. We demonstrated that chronic atrophic gastritis was a major precancerous condition of AEG in the Japanese population, especially Siewert type III which had background mucosal pathology similar to that of GC. Type II AEGs with and without atrophic background showed some clinicopathological differences, and these observations might represent heterogeneous carcinogenic process within type II AEGs. Abstract : Background mucosa of Siewert type II esophagogastric junctional adenocarcinomas less frequently showed atrophic gastritis than that of type III. Background conditions might reflect the heterogeneity of type II tumors.